Abdominal Adiposity Measured by Sonography as a Tool for Determining Disease Risk. (July 2018) - Stigall, A. Nicole; Evans, Kevin D.; Tatarski, Rachel; Pargeon, Rachel L.; Spees, Colleen
A preexperimental cohort study was conducted with 67 overweight cancer survivors. This cohort of participants was screened for baseline body composition and anthropometrics based on a variety of techniques, including body mass index (BMI), dual X-ray absorptiometry–percentage body fat (DXA-android %BF), diagnostic medical sonography (DMS), and waist circumference (WC). The combination of subcutaneous fat layer at the xyphoid and umbilicus compared with BMI, WC, and DXA-android %BF. These variables demonstrated moderately positive association and were statistically significant. A total maximum mean score of DMS measures of subcutaneous and visceral fat was also compared with BMI, WC, and DXA-android %BF. The aforementioned comparison had a moderately positive association and was statistically significant. The sonographic measure of mesentery fat was compared with WC and demonstrated a strongly positive strength of association and was statistically significant. Sonography may be an inexpensive, noninvasive, portable, and valid body composition measure for overweight patients.